2017
DOI: 10.1097/md.0000000000006026
|View full text |Cite
|
Sign up to set email alerts
|

Mini-plate fixation versus suture suspensory fixation in cervical laminoplasty

Abstract: Background:Both the mini-plate fixation and suture suspensory fixation techniques are extensively applied in cervical laminoplasty, but which technique is superior has not been ascertained. The purpose of this meta-analysis is to compare the results between mini-plate fixation and suture suspensory fixation in cervical laminoplasty for the patients with multilevel cervical compressive myelopathy.Methods:PubMed, Embase, the Cochrane library, CNKI, and WANFANG were searched for studies that compared mini-plate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
(12 reference statements)
0
17
1
Order By: Relevance
“…The costeffectiveness benefits of routinely using plates in laminoplasty are still debatable. 3,24 Recently, skipped-level plating has been reported to be an effective cost-saving strategy for laminoplasty surgery. [9][10][11][12] Cheung et al reported a cohort study comparing the outcomes between skipped-level and full-level plating for laminoplasty with an average follow-up of 5 years, they found that skipped-level and all-level plating for open-door laminoplasty yielded similar clinical and radiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The costeffectiveness benefits of routinely using plates in laminoplasty are still debatable. 3,24 Recently, skipped-level plating has been reported to be an effective cost-saving strategy for laminoplasty surgery. [9][10][11][12] Cheung et al reported a cohort study comparing the outcomes between skipped-level and full-level plating for laminoplasty with an average follow-up of 5 years, they found that skipped-level and all-level plating for open-door laminoplasty yielded similar clinical and radiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, increased laminar closure or spring-back has been reported with this technique. [8,9] Spring-back phenomenon or closure, has a reported rate of 10% [9] depending on its definition, and is a major concern in laminoplasty as closure of the laminae opening can lead to renarrowing of the spinal canal and recurrence of symptoms. Since then, mini-plates have been used as a more rigid fixation alternative to maintain the laminae opening.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, mini-plates have been used as a more rigid fixation alternative to maintain the laminae opening. [10,11] Despite apparent clinical benefits [8], mini-plates are costlier. As healthcare providers, this increased cost is a factor that should be considered when designing a management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Mini-plate fixation has been considered better than traditional facet joint suturing technique based on published data. [4,5] Currently, both the mini-plate fixation and anchor screw fixation techniques are widely applied in laminoplasty for treating MCSM, but the scientific support is weak as for which technique is superior.…”
Section: Introductionmentioning
confidence: 99%